2022
DOI: 10.21037/qims-21-509
|View full text |Cite
|
Sign up to set email alerts
|

Altered structural covariance and functional connectivity of the insula in patients with Crohn’s disease

Abstract: Background: Crohn's disease (CD) is a clinically chronic inflammatory bowel disease, which has been shown to be closely related to the brain-gut axis dysfunction. Although traditionally considered to be a limbic region, the insula has also been commonly identified as an abnormal brain region in previous CD-related studies.Methods: Structural magnetic resonance imaging (MRI) and resting-state functional MRI images were acquired from 45 CD patients in remission and 40 healthy controls (HCs). Three neuroimaging a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 71 publications
3
8
0
Order By: Relevance
“…The insula is associated with diverse physiological functions, including interoception, the innate sense of the physiological condition of one's body states (Craig, 2002), and may also play a role in the pathology of psychiatric disorders and cognitive deficits (Goodkind et al, 2015). While insula structure has been associated with childhood internalizing disorders and traumatic experiences (Klabunde et al, 2017), this is one of few studies of childhood-onset CHCs specifically implicating insula structure (Naegel et al, 2014;S. Zhang et al, 2022S.…”
Section: Discussionmentioning
confidence: 99%
“…The insula is associated with diverse physiological functions, including interoception, the innate sense of the physiological condition of one's body states (Craig, 2002), and may also play a role in the pathology of psychiatric disorders and cognitive deficits (Goodkind et al, 2015). While insula structure has been associated with childhood internalizing disorders and traumatic experiences (Klabunde et al, 2017), this is one of few studies of childhood-onset CHCs specifically implicating insula structure (Naegel et al, 2014;S. Zhang et al, 2022S.…”
Section: Discussionmentioning
confidence: 99%
“…CD, as a chronic IBD, primarily affects the gastrointestinal tract. Some recent studies have proposed that the microbiota-gut-brain axis may be a critical contributor in understanding the concomitant mental health issues in IBD and related disorders ( Lv et al, 2018 ; Gracie et al, 2019 ; Thomann et al, 2019 ; Zhang et al, 2022 ). Animal-model research showed that chronic gastrointestinal inflammation might induce anxiety-like behavior and alter biochemistry of the central nervous system in mice ( Mogilevski et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prior CD studies based on functional MRI have demonstrated abnormal neural activity and functional connectivity, regional homogeneity, and amplitude of low‐frequency fluctuations in various regions primarily associated with emotion, pain, and cognitive‐related functions, which would provide information to further understand the neural mechanisms of CD 73 . Moreover, multimodal MRI that combines functional and structural MRI can provide additional information 74 . Prior multimodal studies of voxel‐based morphometry and functional connectivity indicated that differences were observed in the insula, paracentral lobule, cingulate gyrus, and medial frontal gyrus, which are related to the mental state, pain, and quality of life of patients with CD.…”
Section: Role Of Brain Mr Imaging In Gut‐brain Axis Research In CDmentioning
confidence: 99%
“… 73 Moreover, multimodal MRI that combines functional and structural MRI can provide additional information. 74 Prior multimodal studies of voxel‐based morphometry and functional connectivity indicated that differences were observed in the insula, paracentral lobule, cingulate gyrus, and medial frontal gyrus, which are related to the mental state, pain, and quality of life of patients with CD. These neural correlations potentially serve as useful biomarkers for evaluating the treatment efficacy and differential points for diagnosing diseases.…”
Section: Role Of Brain Mr Imaging In Gut‐brain Axis Research In CDmentioning
confidence: 99%